Suicidal ideation in relation to depression, loneliness and hopelessness among university students - Pervin, Mst Maleka; Ferdowshi, Nafiza (Dhaka University Journal of Biological Sciences, 2016)
The purpose of the present study was to examine the relationship between suicidal ideation and depression, loneliness, hopelessness among University students. Study sample is comprised of 112 University students (51 males and 61 females) drawn by using purposive sampling technique. Standard questionnaires were used to obtain the data from the participants in a cross?sectional survey. The obtained data were analyzed by using Pearson product moment correlation and stepwise multiple regression. Results showed that suicidal ideation was positively correlated with depression, loneliness and hopelessness. Stepwise multiple regression analysis further reveals that depression, loneliness and hopelessness significantly predict suicidal ideation among university students. Study limitations and implications are also discussed. Dhaka Univ. J. Biol. Sci. 25(1): 57-64, 2016